Surgical Treatment of Distal Radius Fractures Using Minimally Invasive Plate Osteosynthesis or Open Reduction and Internal Fixation: A Five-Year Comparative Follow-Up Study - Giuseppe Rovere; Pierfrancesco Pirri; Gianmarco Murgante; Vincenzo De Luna; Aurelio Testa; Giovanna Fidone; Francesco Liuzza; Pasquale Farsetti; Fernando De Maio (Applied Sciences)
Distal radius fractures (DRFs) constitute one of the most prevalent injuries in adults. This study compares the clinical and radiological outcomes of intra- and extra-articular DRFs treated with percutaneous Kirschner wires (PKW) or volar locking plates (VLP). Materials and Methods: A retrospective analysis was conducted on 42 patients (aged 18 to 85) treated between 2017 and 2019 with a minimum follow-up of five years. Outcomes were assessed using radiographic parameters and validated clinical scoring systems such as Disabilities of the Arm, Shoulder, and Hand (DASH), Patient-Rated Wrist Evaluation (PRWE), and Mayo Wrist Score (MAYO). Results: Clinical outcomes were better in the VLP group but not statistically significant (p > 0.05). For extra-articular fractures, DASH were 1.5 (VLP) vs. 6.4 (PKW) (p = 0.5007), PRWE were 1.3 (VLP) vs. 2.9 (PKW) (p = 0.4049), and MAYO were 95 (VLP) vs. 86.1 (PKW) (p = 0.2406). For intra-articular fractures, DASH were 6.6 (VLP) vs. 19.7 (PKW) (p = 0.0981), PRWE 12.9 (VLP) vs. 21.1 (PKW) (p = 0.3661), and MAYO 78.9 (VLP) vs. 72.2 (PKW) (p = 0.4503). Conclusions: PKW and VLP showed satisfactory long-term outcomes. VLP fixation allowed better short-term recovery and anatomical restoration, but long-term functional outcomes were comparable.